2006
DOI: 10.1051/forest:2006049
|View full text |Cite
|
Sign up to set email alerts
|

Carbon accumulation in Finland's forests 1922–2004 – an estimate obtained by combination of forest inventory data with modelling of biomass, litter and soil

Abstract: -Comparable regional scale estimates for the carbon balance of forests are needed for scientific and political purposes. We developed a method for deriving these estimates from readily available forest inventory data by using statistical biomass models and dynamic modelling of litter and soil. Here, we demonstrate this method and apply it to Finland's forests between 1922 and 2004. The method was reliable, since the results obtained were comparable to independent data. The amount of carbon stored in the forest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
126
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 169 publications
(140 citation statements)
references
References 53 publications
5
126
0
5
Order By: Relevance
“…In this study we did not take into account the carbon biomass of understory and litter as they represent a small fraction of the total carbon in most forests (Brown 2002). Because we did not have data available for estimating carbon biomass in soils, it was not considered in this study despite the high importance of soil carbon (Liski et al 2006). The review of Nave et al (2010) showed a significant decrease in soil carbon following harvesting.…”
Section: Carbon Measurementsmentioning
confidence: 99%
“…In this study we did not take into account the carbon biomass of understory and litter as they represent a small fraction of the total carbon in most forests (Brown 2002). Because we did not have data available for estimating carbon biomass in soils, it was not considered in this study despite the high importance of soil carbon (Liski et al 2006). The review of Nave et al (2010) showed a significant decrease in soil carbon following harvesting.…”
Section: Carbon Measurementsmentioning
confidence: 99%
“…Using yield tables for a regional scale (Kurz et al, 2009) or quantifying the site index based on environmental factors (Nothdurft et al, 2012;Wang and Klinka, 1996) will help constrain the uncertainties associated with estimating a site index. To enable more precise and comprehensive assessment of South Korean forest C cycles, some important influences on C balance, such as CO 2 fertilization (Bellassen et al, 2011;Luyssaert et al, 2010), N deposition (Luyssaert et al, 2010), leaching (Luyssaert et al, 2010;Piao et al, 2012), forest area changes (Liski et al, 2006;Nabuurs et al, 2003), and management and other disturbances (Jandl et al, 2007;Kurz et al, 2009;Liu et al, 2002;Luyssaert et al, 2010;Zhou et al, 2013) need to be considered.…”
Section: Uncertaintiesmentioning
confidence: 99%
“…One is based on biomass expansion factors (BEFs) ( Chhabra et al, 2002;Jalkanen et al, 2005;Lehtonen et al, 2004;Levy et al, 2004;Liski et al, 2006;Soares and Tomé, 2004) that convert stand volume to stand biomass. The other method is based on models that reflect the allometric relationship between tree biomass and tree variables.…”
Section: Introductionmentioning
confidence: 99%